Quality of Primary Health Care in Brazil: patients'view - Daniela Cristina Moreira Marculino de Figueiredo; Helena Eri Shimizu; Walter Massa Ramalho; Alexandre Medeiros de Figueiredo; Kerle Dayana Tavares de Lucena
ABSTRACT Objective: To describe the evaluation of patients that participated in the National Program for Improving the Access and Quality in Primary Health Care (Programa Nacional de Melhoria do Acesso e da Qualidade na Atenção Básica) for the comprehensive healthcare, the bond and the coordination of care in the country's macro-regions. Method: A descriptive, transversal study, from interviews with 65,391 patients of Primary Health Care, in 3,944 municipalities regarding the use of health services. Results: The professionals seek to solve the patients' problems in their unit (73.1%) but focused mainly on the scope of the appointment (65.6%) and offering care away from the population's reality (69.4%). Difficulties in the rescue of clinical history were referred (50.3%) and in the care performed in other health services (29.2%). Conclusion: The comprehensive health care, the bond and the coordination of care remain challenges to the Primary Health Care in the country, requiring reflections on the implementation of national policies, especially considering the regional diversities in Brazil.